Kadar Protein dan Vitamin C Kue Pukis Dengan Substitusi Tepung Kacang Merah (Phaseoulus Vulgaris L.) dan Tepung Kerang Darah (Anadara Granosa L.) - Fatmawaty Suaib; Retno Sri Lestari; Yulfira Yusuf (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Many Indonesian cake products, such as pukis cakes, generally use wheat flour as raw material even though Indonesia is not a wheat producing country. To reduce dependence on wheat flour, it is necessary to look for local substitutes for wheat flour. One way to diversify local food is making pukis cakes with the substitution of red bean flour and blood cockle flour. Efforts to overcome the problem of anemia are to increase the intake of foods rich in protein and vitamin C such as red beans and blood cockles. This research aims to determine the protein and vitamin C levels of pukis cakes with the substitution of red bean flour and blood cockle flour. This type of research is a pre-experiment using a One Shot Study Case laboratory design with concentration formulas for red bean flour and blood cockle flour respectively 95 g and 5 g, 90 g and 10 g, and 85 g and 15 g. Protein levels were tested using the micro Kjedhal method and vitamin C levels were tested using the iodometric titration method. The results of this study showed that the protein content of pukis cakes by substitution of red bean flour and blood cockle flour increased F0 and F1 by 16.64%, F1 and F2 by 3.85%, F2 and F3 7.54% and vitamin C levels of pukis cakes. Substituting red bean flour and blood cockle flour there was an increase in F0 and F1 by 24.10%, F2 and F3 by 2.14%, and a decrease in the presentation of F1 and F2 -1.71%. Future researchers are expected to conduct further research on the effect of dough storage time on the vitamin C levels of pukis cakes substituted for red bean flour and blood cockle flour. And the processing of local food ingredients can be further improved to produce products that are beneficial for health. Keywords :Pukis Cake 1; Red Beans 2; Blood Clam 3; Protein 4; Vitamin C 5